Enhanced photocatalytic activity towards H2 evolution over NiO via phosphonic acid surface modification with different functional groups. (21st June 2019) - Wang, Jiajia; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Zheng, Zhaoke; Qin, Xiaoyan; Zhang, Xiaoyang; Dai, Ying; Huang, Baibiao
Abstract: Enhancing the photocatalytic activity of NiO towards hydrogen generation (6 times) is achieved by phenyl phosphoric acid (PPA) surface modification. The photocatalytic activity can be further improved by changing PPA to 4-aminophenyl phosphonic acid (PPA-NH2 ), about 10 times, suggesting the functional group plays an important role in improving the activity. A chemical bond (Ni O P) between NiO and organic phosphoric acid was proved by FT-IR spectra. XPS and LSV analysis suggested organic phosphonic acid modification increased the electron density of Ni, which promoted the transformation from Ni 2+ to Ni 0 . Mott-Schottky (M − S) measurement revealed that PPA-NH2 modified NiO processed a larger the space charge layer thickness (dsc ), which enhanced ability towards H2 evolution from dynamical aspect. Highlights: NiO modified by PPA improves photocatalytic H2 production by about 6 times. PPA-NH2 increases the electron density of surface Ni in NiO. Electron donating group (PPA-NH2 ) improves the photocatalytic activity of NiO.